(untitled) (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2020)
Biodiesel produced from sunflower seed oil is environmentally friendly, sustainable and feasible as an alternative to conventional diesel fuel. Sunflower seed oil biodiesel was produced through trans-esterification reaction using 200 g sunflower seed oil (SSO), 40g methanol and 0.8g sodium hydroxide (NaOH) catalyst at 55 ℃ reaction temperature and 120-minute reaction time. The experiment was carried out three times and average results evaluated. High yield of the biodiesel (88.31%) was obtained. The fuel property of the biodiesel product was determined by the American standard for testing and materials (ASTM) fuel tests. Some of the properties includes density (0.79 g/cm3), kinematic viscosity (3.59 mm2/s), dynamic viscosity (6.58x10-3 kgm-1s-1), water content (0.04% mass), acid value (0.36 mg KOH/g), flash point (159 °C) and pour point was found to be -19 °C. The results found to be within the range of American standard for testing and materials (ASTM), the fuel tests show that the biodiesel product from Sunflower seed oil can serve as an alternative source for diesel production.